Effect of walking with an active ankle exoskeleton on the biomechanical responses of the lumbar spine - Rubio, Jose E.; Tong, Junfei; Sundaramurthy, Aravind; Pant, Anup; Nagaraja, Sridevi; Owen, Meredith K.; Samaan, Michael A.; Noehren, Brian; Reifman, Jaques (Frontiers in Bioengineering and Biotechnology, 2025)
ObjectiveMusculoskeletal injuries pose a health threat to U.S. Service members. In particular, the physical demands of walking and running with load carriage contribute to a high incidence of musculoskeletal injuries of the lower back. Active ankle exoskeleton devices are promising technologies that may help mitigate the impact of load carriage on the incidence of these injuries. However, the safe extended use of these devices requires an understanding of their beneficial or detrimental effects on the lumbar spine. In this pilot study, we investigated the impact of walking with an ankle exoskeleton device on lumbar biomechanical responses.MethodsWe collected motion-capture data and computed tomography images for five young, healthy men walking with a 22.7 kg (50-lb) load for 5 km at a speed of 1.3 m/s, with and without an active ankle exoskeleton (ExoBoot EB60). We developed individualized musculoskeletal and finite-element models to characterize the effects of walking distance and ExoBoot use on the trunk flexion angle, joint reaction force at the L4-L5 joint, and stress on the L4-L5 intervertebral disc annulus.ResultsWhile not statistically significant, we found that the peak trunk flexion angle and the peak annulus stress increased by 16% and 12%, respectively, after walking 5 km with the ExoBoot, and by 34% and 25%, respectively, without it. Similarly, the peak L4-L5 joint reaction force minimally increased by 4% with the ExoBoot, while it increased by 22% without the device.ConclusionExoBoot use likely attenuates the effect of fatigue on the lumbar spine induced by walking with load carriage.